Nonlinear Seismic Analysis of a High Concrete Gravity Dam - Lakkundi, Manjunatha; Paul, D. K. (AMC Indian Journal of Civil Engineering, 2020)
Nonlinear dynamic analysis of a high concrete gravity dam is a real complex problem. In this study the dynamical behavior of a high concrete gravity dam has been analyzed by finite element method. The case study is Bhakra concrete gravity dam with the height of 158.049 m. The response subjected to dynamic loading is a combined effect of the dam with foundation system. The concrete damaged plasticity model is used for nonlinear material properties of concrete to simulate the damage induced in the concrete dam under earthquake excitations. Mesh size effect on tensile damage detection of the dam is also carried out. Modeling and analysis work is done by ABAQUS software tool. According to dynamical analysis, results have been calculated, time history of normal stress, displacement of dam at crest level, and their peak responses at different excitations have been compared and investigated.